Hubungan antara Dukungan Keluarga dengan Quality of Life pada Anak Thalasemia Mayor - Azzahra, Nindyas Ayu; Amalia, Linda; Andriyani, Septian (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
Kids diagnosed with thalassemia major must undergo continuou lifelong transfusion therapy, which can have an impact on their overall quality of life. Family support that can improve the quality of life of children with thalassemia includes informational, appreciation, instrumental, and emotional support and Parents have a crucial part in assisting their children in managing the stress and anxiety that often arise due to thalassemia. This research aimed to investigate how family assitance correlates with the quality of life for youngsters diagnosed with thalassemia major. This study uses a quantitative research method with a correlational research design and a cross-sectional approach. The sampling technique used is purposive sampling with a sample size of 60 people. The variables in this study include independent variables, namely family support, while the dependent variable is Quality of life. The instruments used were family support questionnaires according to Friedman's theory and PedQL 4.0 (Pediatric Quality Of Life Inventory). This research took place in the Thalassemia Polyclinic Area of Al-Ihsan Hospital, located in Bandung, West Java Province. Data analysis using the chi-square method. The results showed that the majority had positive family support with an average score of 35,59 as many as 44 people (73,3%) and the majority had a normal quality of life with an average score of 73 as many as 31 people (51,7%). The results of the Statistical analyses yielded a significance level of 0,001 (p value 0,005), there exists a notabele correlation between the two factors. The findings from this research indicate that there is connectiob between familial assistence and quality of life in children with thalassemia major.